AdvancED Flex 4 - Tiwari, Shashank; Elrom, Elad; Schulze, Charlie (Apress : Imprint: Apress, 2010)
AdvancED Flex 4 makes advanced Flex 4 concepts and techniques easy. Ajax, RIA, Web 2.0, mashups, mobile applications, the most sophisticated web tools, and the coolest interactive web applications are all covered with practical, visually oriented recipes. Completely updated for tools new to Flex 4 Demonstrates how to use Flex 4 to create robust and scalable enterprise-grade rich Internet applications Teaches you to build high-performance web applications with interactivity that really engages your users.